Lies from Outer Space: The Martians’ Famous Invasion of New Jersey - Alessandra Calanchi (LED - Edizioni Universitarie di Lettere Economia Diritto, 2021)
Over the course of time, people have been told many lies concerning the Red Planet. Maybe the most renowned one dates back to the late 1880s, when, owing to an error in translation, scientists were led to believe in the existence of canals on its surface – canals instead of channels – which meant that Mars must be inhabited. More recently, in 1976, a lively discussion arose about the “face on Mars”, something that was spotted by the Viking 2 spacecraft in the region of Cydonia and was later dismissed as a mesa whose unusual shadows had cheated the eye. But the biggest lie of all was told in 1938, when a young actor (Orson Welles) decided to play a Halloween trick with the help of the then-rising medium – the radio. It was not really a lie in the strictest sense of the term. It was not a hoax or a fake, either – it was, in narratological terms, what is commonly called the suspension of disbelief pushed to its extreme. In this essay I am going to reconsider this event mainly in the light of two main conditions concerning lying, namely untruthfulness and the intention to deceive. Our specific case is further complicated by a third factor, that is the fact that somebody lies to someone who is believed to be listening in but who is not being addressed. I will also highlight the aftermath of this mass deception which, despite being followed by a number of disclaimers, actually overturned the utopian portrait of Martians, initiating a long literary and filmic theory of alien invasions.